PENGARUH SUHU DAN LAMA PEMANGGANGAN TERHADAP TINGKAT KESUKAAN DAN KANDUNGAN GIZI SNACK FOOD BARS BERBAHAN DASAR TEPUNG PISANG GOROHO DAN TEPUNG AMPAS TAHU - Rahmiyati Kasim; Siti Aisa Liputo; Marleni Limonu; Fadhilah Pratiwi Mohamad (Jurnal Technopreneur (JTech), 2018)
The research aims to understand the effect of temperature and roasting time on the level to the preference level and nutrition value of snack food made from goroho banana flour and less of tofu flour. This snack food bars is good for diabetics, because using raw materials with low glicemic index. Design use is a complete random ( ral ) factorial, where consisting of 2 factors, the first is the temperature roasting consisting of 2 standard: 130 0C, 160 0C and the second factor is roasting time consisting of 2 standard: 30 minutes, 60 minutes. Consisting of four combinations treatment each treatment repeated three times, so composed of twelve units experiment. The research consisting of some stages that is the first stage is preparation raw materials which includes making banana flour goroho and flour dregs know , then making snack food bars and testing organoleptik and analysis proximate. The data obtained analyzed using ANNOVA. When there is significant differences between treatment, then continued with BNT test different (different real smallest ).The results of the analysis variety of results showed that combination treatment temperature and roasting time had have real impact on colors, flavor, texture, water content, protein content, ash content, fat content and carbohydrate content but not have real impact to the odor of snack food bars. A snack food bars made from the banana flour goroho and less of tofu flour resulting in this research containing water content as much as 7,03-29,82 % , protein content 8,08-10,42 % , fat content 3,88-7,61%, ash content 1,05-1,97 % , as much as 51,10-79,07 carbohydrate content. Keywoard : Snack food bars, temperature and period of roasting, diabetics, goroho bananan, tofu flour